Comparative Neuroanatomy of the Mechanosensory Subgenual Organ Complex in the Peruvian Stick Insect, Oreophoetes peruana - Strauß, Johannes; Justus Liebig University Giessen (My University, 2022)
The subgenual organ complex in the leg of Polyneoptera (Insecta) consists of several chordotonal organs specialized to detect mechanical stimuli from substrate vibrations and airborne sound. In stick insects (Phasmatodea), the subgenual organ complex contains the subgenual organ and the distal organ located distally to the subgenual organ. The subgenual organ is a highly sensitive detector for substrate vibrations. The distal organ has a characteristic linear organization of sensilla and likely also responds to substrate vibrations. Despite its unique combination of sensory organs, the neuroanatomy of the subgenual organ complex of stick insects has been investigated for only very few species so far. Phylogenomic analysis has established for Phasmatodea the early branching of the sister groups Oriophasmata, the Old World phasmids, and Occidophasmata, the New World phasmids. The species studied for the sensory neuroanatomy, including the Indian stick insect Carausius morosus, belong to the Old World stick insects. Here, the neuroanatomy of the subgenual organ complex is presented for a first species of the New World stick insects, the Peruvian stick insect Oreophoetes peruana. To document the sensory organs in the subgenual organ complex and their innervation pattern, and to compare these between females and males of this species and also to the Old World stick insects, axonal tracing is used. This study documents the same sensory organs for O. peruana, subgenual organ and distal organ, as in other stick insects. Between the sexes of this species, there are no notable differences in the neuroanatomy of their sensory organs. The innervation pattern of tibial nerve branches in O. peruana is identical to other stick insect species, although the innervation pattern of the subgenual organ by a single tibial nerve branch is simpler. The shared organization of the organs in the subgenual organ complex in both groups of Neophasmatodea (Old World and New World stick insects) indicates the sensory importance of the subgenual organ but also of the distal organ. Some variation exists in the innervation of the chordotonal organs in O. peruana though a common innervation pattern can be identified. The findings raise the question for the ancestral neuroanatomical organization and innervation in stick insects.
Keywords: Neuroanatomy; Chordotonal organ; Peripheral nervous system; Mechanoreception; ddc:570